Transforming Foodways. Sustainability Sensemaking Processes among Finnish Food Companies - Jungell-Michelsson, Jessica; suomi, suomi (Ethnologia Fennica, 2022)
Food companies are central actors in driving sustainability transformations at the interface of production and consumption. Still, only limited attention has been directed to how sustainability-related meanings are being created within various food industry organizations. In this article, we explore the characteristics of the sustainability sensemaking and -giving processes among food companies and analyze how these processes influence sustainability-related transformations of current foodways. Our analysis is based on qualitative data (transcripts and notes) from interviews with managers from 15 Finnish food companies. By using organizational sensemaking literature, we shed light on the companies’ cultural talk and social meaning creations of sustainability. Our findings indicate that food companies’ sustainability sensemaking is an intra- and inter-organizational, social process occurring between the individual and organizational spheres of the organizations. Food companies act as sensegivers, as they actively communicate with stakeholders to achieve the position of a knowledgeable sustainability forerunner. Sustainability has been normalized in the talk and action of food companies, but the discursive space offered by them is limited to weak sustainability perspectives. While socio-material transgressions of current foodways may emerge, we argue that a shift from communicating and commercializing sustainability to a focus on ecological material aspects and ecological sensemaking is essential for transforming foodways towards strong sustainability.
Keywords: sustainability; sustainable food systems; foodways; organizations; food companies; sensemaking; sensegiving